Dakwah Melalui Ilustrasi Kartun: Pendekatan Komunikasi Visual dalam Penyebaran Nilai-Nilai Keislaman Kontemporer - Dadiamar, Firlyana; Muhlis, Atjep; Wahyuddin, Aep (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2014)
This study aims to find out as a whole about the meaning of denotation, connotation and myth contained in da'wah through the cartoon illustration of the @Taqwart Instagram account based on Semiotic Analysis, with descriptive study research methods that use a qualitative approach and the framework of thinking Semiotics Analysis on Roland Barthes theory. Based on the results of the study, several conclusions emerged as follows: 1) There is advice that is represented in the form of color, shape and writing on the denotative meaning 2) The meaning of connotation is in the form of a message for muamalah to its relation to aqidah. 3) The meaning of myths related to morality.